The Current Position of Science Development in the World and in Azerbaijan - Solmaz Aghazaki Abidi, Sugra Ingilab Humbatova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Science, knowledge, scientific output and scientific enterprises are leading resource which possesses decisive significant in the field of general development and especially in economical development. It was founded that the role of number of staff dealing with the research is lower in executed scientific technical works for objective reasons. It is explained as follows: their potential is not fully used; In order to realise their potential the favourable environment, conditions and initial capital are not at the same level. Correlation and regression equation (OLS) structured according to the mathematical economy methods and dependency among variables are determined. Application of obtained and will be obtained scientific achievements, inventions are very weak in strong competition in globalization and international free economic conditions.